What you see is what you get: lidar applications in the northern Adriatic coastal regions - Doneus, Nives; Doneus, Michael (Journal of Greek Archaeology, 2025)
Airborne lidar has played a distinctive role in remote sensing case studies in the Mediterranean context for the last decade. The new possibilities offered by lidar methodology have made it a valuable tool in a number of Mediterranean countries, including Greece and Croatia. The coastal landscapes of both countries share similarities due to the influence of common factors like relief, climate, and vegetation. Furthermore, the numerous islands in both countries have played a significant role in long-distance maritime trade and communication throughout history. While the historical development of land use on the islands of the two countries may have differed, the lidar data indicate comparable remains of land use resulting from the Mediterranean agricultural practices of agro-pastoral societies. The challenges of preserving archaeological heritage in coastal areas are also similar. They can be attributed mainly to the effects of extensive (tourist) construction and development, or to the impact of sea-level rise and the associated risks of flooding and erosion. Given these similarities, it seems beneficial to present an overview of Croatian case studies in a volume dedicated to lidar studies in Greece, as airborne lidar represents an effective approach for the documentation and interpretation of the archaeological heritage in both countries.